Modeling and Parameter Identification of the Slung Load System of an Unmanned Rotorcraft using a Flexible Cable - Lee, Byung-Yoon; Moon, Gun-Hee; Lee, Dong-Yeon; Tahk, Min-Jea; Oh, Hyun-Shik (International journal of aeronautical and space sciences, 2017)
In this paper, we propose a method to identify the parameters of a rotorcraft slung load system using the modal characteristics of a flexible cable. The proposed method estimates the length of the cable and the mass of the payload by means of a frequency analysis. Dynamic equations of the slung load system with the flexible cable are derived using UdwadiaKalaba equation (UKE) in order to build a simulation program, and the similarity of the simulated slung load movement is verified by comparison with flight test results. Using the computer simulation program, we show that the proposed method works well within various parameter ranges. KCI Citation Count: 1